Maternal nucleotide supplementation improves the intestinal morphology and immune function in lipopolysaccharide-challenged newborn piglets - Li, Qiming; Hung, Ifen; Bai, Kaiwen; Wang, Tian (Frontiers in Veterinary Science, 2022)
This study aimed to evaluate the effects of maternal nucleotide (NT) supplementation on intestinal morphology and immune function in lipopolysaccharide-challenged newborn piglets. At 85 d gestation, 12 sows were selected and assigned to two groups: the CON group (basal diet, n = 6) and the NT group (basal diet with 1 g/kg NT mixture, n = 6). After parturition, newborn piglets were collected without suckling. Piglets from the CON group were intraperitoneally injected with sterile saline or lipopolysaccharide (LPS, 10 mg/kg body weight), and divided into the C-CON (n = 6) and C-LPS groups (n = 6). Piglets from the NT group received the same treatment and were divided into the N-CON (n = 6) and N-LPS groups (n = 6). The blood and small intestinal samples of piglets were collected 1 h after injection. The results showed that: (1) maternal NT supplementation increased the concentrations of serum complement C3 and C4 (P < 0.05), and suppressed the increase in serum hypersensitive C-reactive protein in LPS-challenged newborn piglets (P < 0.05); (2) maternal NT supplementation increased the villus height and the ratio of villus height to crypt depth in the duodenum of newborn piglets (P < 0.05) and inhibited the LPS-induced decrease in the villus height in the jejunum and ileum (P < 0.05). (3) The LPS-induced increased levels of interleukin-6 in the jejunum and tumor necrosis factor-α in the ileum of newborn piglets were suppressed by maternal NT supplementation (P < 0.05). (4) In the jejunum of newborn piglets, maternal NT supplementation inhibited the LPS-induced increase in toll-like receptor 4 (TLR4) mRNA and protein expression (P < 0.05) and the decrease of nuclear factor-κB inhibitor α (IκBα) protein expression (P < 0.05). In the ileum, piglets had a lower nuclear factor-κB (NFκB) mRNA expression in the NT groups than the CON groups (P < 0.05), and maternal NT supplementation suppressed the decrease of IκBα mRNA in LPS-treated piglets (P < 0.05). In conclusion, maternal NT supplementation could promote the intestinal development and immune function of newborn piglets, and may improve LPS-induced intestinal inflammatory responses via the TLR4/IκBα/NFκB pathway.